Group Counseling with Expressive Writing Techniques to Reduce Student Academic Stress - Fatimah, Siti (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
Academic stress is a condition that makes students feel pressured because academic demands are difficult to overcome. This research aims to determine the effectiveness of expressive writing techniques in reducing the academic stress of class X students at SMA Negeri 1 Gambut. This study is quantitative-oriented research that applies experimental methods. This research was conducted at SMA Negeri 1 Gambut, and the research sample was obtained through the results of a questionnaire using a purposive sampling technique, totaling 6 people. Data collection used the ESSA scale instrument (Educational Stress Scale for Adolescents). Data analysis uses parametric analysis, namely the t test. The results of the research show that the application of group counseling using expressive writing techniques can reduce the academic stress of class X students at SMA Negeri 1 Gambut.Keywords: Academic Stress, Group Counseling, Expressive Writing Techniques